Comparison of Mechanical Properties of Deformed Steel Wire Determined using Contact and Laser Extensometers - Monge Sandí, Ana Lorena (2014)
This research paper presents the study of 16 samples of deformed steel wires, which were applied to tensile tests using two types of extensometers: contact and laser. The main objective of the analysis is to determine if the results obtained by the laser extensometer have sufficient accuracy to determine the tensile mechanical properties properly, in order to validate the use if laser extensometer in standard laboratory tensile tests, as well as determine a methodology of the obtainment of the mechanical properties of steel samples with an undefined yield point. From the results, it is concluded that the laser extensometer, as well as the methodology used, produce results which are quantitative similar to the contact extensometer, therefore validating its use for standard laboratory tensile testing of materials with an undefined yield point.